PENGGUNAAN VIDEO SKATEBOARD SEBAGAI PERSONALBRANDING PROFESIONAL SKATEBOARDING YAYANSETYA - Vitto Widha Kusuma; Estu Widiyowati; Buddy Riyanto; Haryo Kusumo Aji (Solidaritas, 2025)
The phenomenon of using digital media, particularly skateboard videos, has increasingly developed as an essential medium for skateboarders to build their identity and professional image. Videos serve not only as entertainment or documentation of activities but also as a strategic communication tool that highlights uniqueness, consistency, and individual characteristics. This study aims to analyze the use of skateboard videos as a form of personal branding by Yayan Setya, a professional skateboarder from Surakarta. This research employs a descriptive qualitative method with a case study approach. Data were collected through observation, interviews, and documentation of skateboard videos produced and published by Yayan Setya. The analysis focuses on how audio visual elements, tricks, style, and Consistency in video production contribute to the construction of his personal branding and distinguish him from other skateboarders. The findings reveal that skateboard videos play a significant role in shaping Yayan Setya’s personal branding. The videos function as documentation of skill development, a audio visual communication medium to express identity, and a personal marketing tool to expand audience reach. Yayan’s personal branding is formed through authenticity, consistency, and his distinctive style presented in each of his works. This study concludes that skateboard videos can serve as an effective strategy for skateboarders to build a professional image, broaden networks, and enhance career opportunities. Keywords: Skateboard Video, Personal Branding, Professional Skateboarder, Yayan Setya.